Can a repeated sprint ability test help clear a previously injured soccer player for fully functional return to activity? A pilot study - Padulo, J.; Attene, G.; Ardigo, L. P.; Bragazzi, N. L.; Maffulli, N.; Zagatto, A. M.; Dello Lacono, A. (Clinical Journal of Sport Medicine, 2017)
Objective: To investigate the effects of fatigue induced by a repeated sprint ability (RSA) test on the neuromuscular responses of soccer players with a recent history of lower limb injuries (CH) and a matched control group in good fitness condition (GH). Design: This was a case-control study. Participants: Nine CH and 9 GH. Independent Variable: Allocation to CH or GH. Main Outcome Measures: Each player was assessed for blood lactate concentration and jumping performance [squat jump (sJ) and countermovement jump (CMJ)] before/after RSA. Post-RSA rate of perceived exertion (RPE) was obtained. Receiver operating characteristic analysis was performed to calculate RSA sensitivity and specificity in distinguishing between CH and GH. intraclass correlation coefficient was used to assess reliability. Results: No baseline differences were found for any variable. ASJ before/after RSA was -14 ± 2% and -5 ± 2% in CH and GH, respectively (P < 0.05). ACMJ before/after RSA was -15 ± 2% and -7 ± 2% in CH and GH, respectively (P < 0.05). ASJ-based and ACMJ-based (before/after RSA) area under curve (AUC) resulted in 0.90 ± 0.07 and 0.86 ± 0.09, respectively, with both AUCs differentiating between CH and GH with 77.78% sensitivity and 88.89% specificity. Pooled AUC resulted in 0.88 ± 0.06. Intraclass correlation coefficient was high (0.85/0.97). Conclusions: Repeated sprint ability is a simple, low-cost field test potentially able to assist in clinical decision making for return to sport. ABSTRACT FROM AUTHOR